The Need for a 7-day Therapy Service on an Emergency Assessment Unit. (January 2014) - Robinson, Anna; Lord-Vince, Hannah; Williams, Rebecca
This practice analysis acknowledges the changing nature of healthcare, recognizing the need for a 7-day therapy service on an Emergency Assessment Unit within the acute sector. A critical reflection on practice is offered to share the experiences of trialling a 7-day therapy service as a solution to managing today's political, economic, and demographic challenges. A 12-month pilot of 4-hour therapy shifts at the weekend demonstrated therapists could discharge 40% of patients assessed on the Emergency Assessment Unit; thus evidencing the need for a permanently funded 7-day service to sustain these results long term. Improved access to therapy on a Saturday and Sunday enhances equality of service provision, patient outcomes and weekend discharge rates. The findings are relevant to all occupational therapists and physiotherapists working in the acute sector.